Nutritional knowledge, attitudes, and practices among residents in the Northeast areas of China during the COVID-19 epidemic - Hou, Liyan; Xia, Xueyan; Du, Ying; Zhang, Yu; Li, Shuangshuang; Liu, Wen; Zhao, Jie; Wang, Ke; Zhang, Lei; Wang, Qingshan (Frontiers in Public Health, 2024)
Background The coronavirus disease 2019 (COVID-19) due to SARS-CoV-2 infection continues to affect the daily life of communities worldwide. Nutrition is a vital determinant of overall health. Given the lack of specific drugs for COVID-19 and incomplete vaccination coverage, optimizing nutrition appears to be one of the most cost-effective means of enhancing immunity. Therefore, this study was designed to evaluate nutrition-related knowledge, attitudes, and practices (KAP) to offer insights into the personal determinants of dietary behavior during COVID-19 pandemic in four major cities within the Northeast region. Methods This cross-sectional study was conducted between January and December 2022 using a self-administered questionnaire. The data were entered in EpiData V-3.02 and analyzed using SPSS version 26. Binary logistic regression analysis was also employed to examine the association between dependent and independent variables. Results A total of 4,092 respondents were included in the study. Most of the respondents demonstrated had inadequate nutrition knowledge, 26% of them provided ≥60% of correct answers. About one-third of the respondents were knowledgeable about the daily levels of oil, salt, milk, water, vegetables and fruits for adults. Furthermore, our results showed that 60.6% of participants held positive attitudes toward healthy eating. Additionally, only 54.6% of the participants have heathy dietary practices during COVID-19 pandemic. Binary logistic regression analysis showed that the following characteristics were associated with displaying unhealthy dietary behaviors: being men, having a lower education level, having a family income of 10,000–19,999 and more than 20,000, being resided in Harbin, Shenyang, and Changchun. Importantly, the strongest associations were observed between poor dietary knowledge and unhealthy eating behaviors. Similarly, dietary attitudes were strongly associated with healthy dietary behaviors when the effects of other factors were excluded; responders with negative attitudes were more likely to exhibit unhealthy eating behaviors. Conclusion Our findings suggest that residents in the Northeast China possessed a relatively low level of nutritional knowledge, which directly influenced their dietary practices during the COVID-19 pandemic. This study provides valuable insights into the cross-sectional description and key factors related to nutrition-related KAP, serving as a basis for future policymaking to respond more effectively to health crises.